Traditional Puppetry as Political Philosophy: Evaluating Wayang Kulit Narratives in the Context of Global Leadership Deficits - Iva Ariani; Shoim Mardhiyah; Nabiel Syahilabi Rajasa (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
The modern leadership crisis is increasingly characterized by declining public trust, weakening moral legitimacy, and the dominance of instrumental power over ethical responsibility. This study employs a qualitative interpretive approach based on library research, utilizing primary data from standardized Wayang Kulit manuscripts (Mahabharata cycle) and secondary data from scholarly literature on political theory and Javanese philosophy. Data were collected through systematic documentation and close reading techniques, while analysis was conducted using a hermeneutic-semiotic approach to interpret symbols, narratives, and character relations. Theoretical frameworks from Weber’s legitimacy theory, Foucault’s concept of power, and Gramsci’s hegemony were applied to analyze the construction of power and legitimacy. Data validity was ensured through source triangulation and cross-referencing with established academic studies. The findings indicate that wayang characters embody distinct leadership archetypes: Arjuna represents reflective and disciplined leadership grounded in self-control and spiritual awareness; Bima symbolizes assertive and justice-oriented leadership driven by courage and moral firmness; while the Punakawan figures, particularly Semar, function as moral critics who articulate collective ethical consciousness and provide checks on power. These characteristics demonstrate that leadership in wayang is not merely hierarchical but dialogical and ethically grounded, offering relevant insights for contemporary leadership practices that require accountability, integrity, and responsiveness to public values. The results confirm that local cultural heritage can serve as a source of critical insight for fostering ethical and responsible leadership. This study contributes to the expansion of wayang studies into political legitimacy theory and demonstrates that cultural narratives can provide a reflective ethical framework for addressing the challenges of modern leadership.